Six decades of change in a Mediterranean port fouling assemblage: winners and losers in the era of global change - Alessandro Abate; Giorgio Bavestrello; Francesca Garaventa; Francesco Enrichetti; Marco Faimali; Carla Morri; Veronica Piazza; Beatrice Ridella; Carlo Nike Bianchi; Martina Canessa (Estuarine, Coastal and Shelf Science, 2026)

Distribution of the echiurid worm Bonellia viridis Rolando, 1822 along the Ligurian Coast, North-Western Mediterranean Sea - Martina Canessa; Marzia Bo; Francesco Enrichetti; Margherita Toma; Giorgio Bavestrello (Estuarine, Coastal and Shelf Science, 2026)

Competitive overgrowth of the zoantharian Savalia savaglia by the sponge Crambe crambe in the Mediterranean Sea - Martina Canessa; Giorgio Bavestrello; Egidio Trainito (Marine Biodiversity, 2025)
Savalia savaglia is one of the few zoantharians capable to grow with a parasitic habitus, infesting damaged gorgonians, such as Eunicella spp., Paramuricea sp., Leptogorgia spp., and antipatharians. It causes tissue necrosis in its hosts and progressively overgrows their skeleton with its own coenenchyme. While previous studies have mainly focused on its distribution, biology, ecology, and conservation, little information is available about its growth patterns and ecological interaction with other benthic organisms. A photographic monitoring of the same S. savaglia specimen over time (2018 and 2025) was carried out within the C zone of the Tavolara—Punta Coda Cavallo Marine Protected Area (NE Sardinia, Tyrrhenian Sea). The image analysis revealed a progressively overgrown of this colony by the encrusting orange sponge Crambe crambe observed. After seven years, the covered portion increased of about 185 cm2 y -1 . The case here described represents the first documented instance of S. savaglia losing a competitive interaction with another benthic organism, indicating that the latter is not always a winner. Probably, the sponge’s aptitude to spatial competition and environmental tolerance facilitates its expansion at the expense of S. savaglia, particularly when the latter’s colony integrity is already compromised or exhibits reduced resilience to disturbance.

Different colonization patterns of various natural substrata in the harbour environment - Martina Canessa; Filippo Castelli; Marta Domeniconi; Laura Gaggero; Francesca Garaventa; Elisa Monteleone; Veronica Piazza; Giorgio Bavestrello (Biofouling, 2025)

Are shallow-water hydrothermal vents stable? A comparison of published maps of the Paleochori Bay (Milos, Greece) systems twenty years apart - Alice Oprandi; Carlo Nike Bianchi; Carla Morri; Martina Canessa (Continental Shelf Research, 2025)

Shedding Light on the Italian Mesophotic Spongofauna - Margherita Toma; Marzia Bo; Marco Bertolino; Martina Canessa; Michela Angiolillo; Alessandro Cau; Franco Andaloro; Simonepietro Canese; Silvestro Greco; Giorgio Bavestrello (Journal of Marine Science and Engineering, 2024)
An analysis of 483 remotely operated vehicle (ROV) dives carried out along the Italian coast on hard substrata at mesophotic depths (40–200 m) allowed an overview of the rich sponge diversity (53 taxa) of the deep continental platform to be obtained for the first time. About 40% of the potential actual species diversity was recognisable using ROV, suggesting that this group is among the richest yet underestimated using this technology in contrast to other megabenthic taxa. Additionally, the study allowed us to gather data on the current basin-scale distribution and bathymetric limits of five common and easily identifiable demosponges with up to 55% occurrence in the explored sites: Aplysina cavernicola, the group Axinella damicornis/verrucosa, Chondrosia reniformis, Foraminospongia spp., and Hexadella racovitzai. Four of these latitudinal distributions were characterised by high occurrence in the Ligurian Sea and a progressive decrease towards the south Tyrrhenian Sea, with an occasional second minor peak of occurrence in the Sicily Channel. In contrast, Foraminospongia spp. showed a maximum occurrence on the offshore reliefs and a second one in the North–central Tyrrhenian Sea, while it was almost absent in the Ligurian Sea. Trophic and biogeographic reasons were discussed as possible causes of the double-peak distributions. The vertical distributions support a more consistent occurrence of all considered taxa in deeper waters than previously known. This suggests that they may more typically belong to the mesophotic realm than the shallow waters, owing to a more extensive sampling effort in the deeper depth range. The five target taxa are typical or associated species of seven reference habitats in the recently revised UNEP/SPA-RAC classification. However, they may create such dense aggregations that they should be listed as new facies in the abovementioned classification.

Micro-scale distribution of Chthamalus stellatus Poli, 1791 is driven by the mineralogical properties of the substrate - Martina Canessa; Andrea Costa; Laura Gaggero; Alessandra Moreni; Federica Passarelli; Giorgio Bavestrello (Estuarine, Coastal and Shelf Science, 2024)

Intense bioturbation by the irregular sea urchin Spatangus purpureus in a Mediterranean maërl bed - Martina Canessa; Giorgio Bavestrello; Egidio Trainito (Marine Biodiversity, 2024)

The paleo-community of the Sciacca red coral - Giorgio Bavestrello; Federico Betti; Lucio Calcagnile; Martina Canessa; Marina D’Elia; Gianluca Quarta; Marzia Bo (Facies, 2023)
The sub-fossil red coral deposits of Sciacca (Sicily Channel) have attracted scientific attention for nearly 150 years. Their origin and formation have been long questioned and investigated, given the fact that they represent one of the most intriguing geobiological events ever to occur in the Mediterranean basin. Less attention was given to the paleo-community associated with the sub-fossil coral. Radiocarbon age determinations, in particular, were provided only for red coral, neglecting the possibility of understanding which species were simultaneously present in the coralline paleo-community and which was their role. The study of cemented coral rubble pieces revealed that Corallium rubrum covered the largest time interval (more than 3000 years) and was contemporary to many secondary epibionts over two millennia and to Madrepora oculata for about 500 years; this last finding suggested that an uncommon co-dominance between the two structuring species occurred in the nearby living communities. The lack of Fe–Mg deposits on the cemented coral rubbles coupled with the low bioerosion rate of the red coral skeletons by the demosponge Siphonodictyon coralliirubri (assessed through the analysis of the erosive paleo-scars) suggested that the deposits met with a rapid sediment cover-up. Moreover, for the first time, the analysis of a piece of cemented coral rubble of sub-fossil red coral coming from Sardinian waters confirmed that, albeit to a lesser extent, the conditions favouring the preservation of dead corals can occur also in different localities far from Sciacca.

Leptogorgia sarmentosa (Anthozoa: Octocorallia) in NE Sardinia (Mediterranean Sea): distribution and growth patterns - Martina Canessa; Giorgio Bavestrello; Egidio Trainito (Marine Biodiversity, 2023)
Distribution and occurrence data of the sea fan Leptogorgia sarmentosa (Esper, 1791) in the Mediterranean Sea were updated thanks to new photographic surveys, highlighting the presence of the species off NE Sardinia and, in particular, in the Tavolara-Punta Coda Cavallo Marine Protected Area (TPCCMPA). The estimated average distance among colonies strongly suggests that they are not able to sexually reproduce and that they probably can be considered a sterile pseudo-population supported by inputs of larvae from the Italian mainland coast towards Sardinia. The putative conveyor belt for larval input to this area is a small permanent gyre (the North-Tyrrhenian Gyre) counterclockwise moving from the Italian to the Sardinian coasts. In TPCCMPA, the growth of one colony settled at 30 m depth was investigated across 7 years (2016–2022). The morphometric parameters indicated a linear development of the colony, in terms of branch development and 3D complexity estimated through the fractal dimension. The observed growth rates were not regular but were reached through a highly variable positive and negative oscillation. A significant correlation was obtained between growth rate and average Autumn and Winter water temperature, suggesting that somatic growth occurs in these periods. In the context of long-lasting elevated seawater temperatures and local damage linked to fishing activities, L. sarmentosa was confirmed to be a resilient species compared with other erect seascape components, like other gorgonians and sponges.

Basin-scale occurrence and distribution of mesophotic and upper bathyal red coral forests along the Italian coasts - MARGHERITA TOMA; MARZIA BO; RICCARDO CATTANEO-VIETTI; SIMONEPIETRO CANESE; MARTINA CANESSA; RITA CANNAS; FRINE CARDONE; LAURA CARUGATI; ALESSANDRO CAU; GIUSEPPE CORRIERO; MARIA CRISTINA FOLLESA; MARIA MERCURIO; et al. (Mediterranean Marine Science, 2022)
The analysis of 879 ROV dives carried out along the Italian coasts on hard substrata at mesophotic and upper bathyal depths (40-775 m) allowed us to evaluate the current basin-scale presence, relative abundance, bathymetric limits, and habitat preferences of one of the most charismatic Mediterranean habitat-former anthozoan species, Corallium rubrum (Linnaeus, 1758). The species is widespread, and its occurrence ranged from 13% of the explored sites in Ionian Calabria to a hotspot of approximately 80% in Sardinia. Population relative densities were generally low (

Sponges associated with stylasterid thanatocoenosis (Cnidaria, Hydrozoa) from the deep Ross Sea (Southern Ocean) - Gabriele Costa; Giorgio Bavestrello; Simonepietro Canese; Martina Canessa; Claudio Mazzoli; Paolo Montagna; Stefania Puce; Stefano Schiaparelli; Marco Bertolino (Polar Biology, 2022)

The sub-fossil red coral of Sciacca (Sicily Channel, Mediterranean Sea): colony size and age estimates - Giorgio Bavestrello; Marzia Bo; Lucio Calcagnile; Martina Canessa; Marisa D’Elia; Gianluca Quarta; Federico Spagnoli; Riccardo Cattaneo-Vietti (Facies, 2021)
The Mediterranean red coral, Corallium rubrum (L.), has been a valuable economic resource for more than 2000 years. The Sicily Channel and surrounding areas are one of the most famous red coral fishing grounds of the whole region, hosting the deepest ever found living colonies and large sub-fossil red coral deposits; the so-called Sciacca banks are a unique location in the whole Mediterranean Sea. In this paper, a morphometric description of this sub-fossil population is presented for the first time from studies of colonies in the collection of several coral factories from Torre del Greco (Naples), with radiocarbon age estimations and growth rate evaluations. From the results of this study, after several thousand years Sciacca red coral colonies maintained the organic matrix structure with evident annual discontinuities, allowing estimations of the annual growth rate (about 0.3 mm/year) and the average population age (about 33.5 years). These resulting data are similar to the values determined for deep-dwelling living red coral populations. The radiocarbon dating evidenced a range of ages, from 8300 to 40 years before 1950 CE, mostly falling between 2700 and 3900 YBP, suggesting that colonies accumulated over a wide span of time. In view of the tectonically active nature of the area, several catastrophic events affected these ancient populations, maintaining them in a persistent state of early-stage, structurally similar to the those in current over-exploited areas.